PRAK-03202: A triple antigen virus-like particle vaccine candidate against SARS CoV-2. Issue 10 (October 2021) - Mazumder, Saumyabrata; Rastogi, Ruchir; Undale, Avinash; Arora, Kajal; Arora, Nupur Mehrotra; Pratim, Biswa; Kumar, Dilip; Joseph, Abyson; Mali, Bhupesh; Arya, Vidya Bhushan; Kalyanaraman, Sriganesh; Mukherjee, Abhishek; et al.
Abstract: The rapid development of safe and effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) is a necessary response to coronavirus outbreak. Here, we developed PRAK-03202, the world's first triple antigen virus-like particle vaccine candidate, by cloning and transforming SARS-CoV-2 gene segments into a highly characterized S. cerevisiae -based D-Crypt™ platform, which induced SARS CoV-2 specific neutralizing antibodies in BALB/c mice. Immunization using three different doses of PRAK-03202 induced an antigen-specific (spike, envelope, and membrane proteins) humoral response and neutralizing potential. Peripheral blood mononuclear cells from convalescent patients showed lymphocyte proliferation and elevated interferon levels suggestive of epitope conservation and induction of T helper 1-biased cellular immune response when exposed to PRAK-03202. These data support further clinical development and testing of PRAK-03202 for use in humans. Highlights: We developed the world's first triple antigen VLP vaccine candidate-PRAK-03202. PRAK-03202 can induce neutralizing antibodies against SARS CoV-2. PRAK-03202 can induce an IFN-γ response in convalescent patient sera. IgG antibody responses against the novel PRAK-03202 persisted for months. Abstract : Virus like particle; Vaccine; Humoral immune response; Convalescent COVID-19 patients; Electron microscopy.